Structural study of the zinc and cadmium complexes of a type 2 plant (Quercus suber) metallothionein: Insights by vibrational spectroscopy (Biopolymers, 2007)
Zn- and Cd-complexes of Quercus suber metallothionein (QsMT) were obtained by in vivo-synthesis, in order to obtain physiologically representative aggregates, and characterized by spectrometric and spectroscopic methods. The secondary structure elements and the coordination environments of the metal binding sites of the two aggregates were determined, as well as the main metal-containing species formed. The results obtained from the analysis of the Raman and IR spectra reveal that these metal-MT complexes predominantly contain b-sheet elements (about 60%), whereas they lack ahelices. These structural features slightly depend on the divalent metal bound. In particular, Cd II binding to QsMT induces a slight increase of the b-sheet percentage, as well as a decrease in b-turn elements with respect to Zn II binding. Conversely, the in vivo capability of QsMT to inglobe metal and sulﬁde ions is metal-depending. Spectroscopic vibrational data also conﬁrm the presence of sulﬁde ligands in the metal clusters of both Zn- and Cd-QsMT, while the participation of the spacer His residue in metal coordination was only found in Cd-QsMT, in agreement with the CD results. Overall data suggest different coordination environments for Zn II and Cd II ions in QsMT